Silent performances: Are "repertoires" really post-Kuhnian?. (February 2017) - Sample, Matthew
Abstract: Ankeny and Leonelli (2016) propose "repertoires" as a new way to understand the stability of certain research programs as well as scientific change in general. By bringing a more complete range of social, material, and epistemic elements into one framework, they position their work as a correction to the Kuhnian impulse in philosophy of science and other areas of science studies. I argue that this "post-Kuhnian" move is not complete, and that repertoires maintain an internalist perspective. Comparison with an alternative framework, the "sociotechnical imaginaries" of Jasanoff and Kim (2015), illustrates precisely which elements of practice are externalized by Ankeny and Leonelli. Specifically, repertoires discount the role of audience, without whom the repertoires of science are unintelligible, and lack an explicit place for ethical and political imagination, which provide meaning for otherwise mechanical promotion of particular research programs. This comparison reveals, I suggest, two distinct modes of scholarship, one internalist and the other critical. While repertoires can be modified to meet the needs of critical STS scholars and to completely reject Kuhn's internalism, whether or not we do so depends on what we want our scholarship to achieve. Highlights: I argue that "repertoires" retain a form of Kuhnian internalism. "Sociotechnical imaginaries" exemplify more symmetrical treatment of scientific change. "Repertoires" should be modified to capture ethics, politics, as well as audience. Picking a framework means choosing between competing visions for STS work in society.